Molecular Changes in Dengue Envelope Protein Domain III upon Interaction with Glycosaminoglycans - James G. Hyatt; Sylvain Prévost; Juliette M. Devos; Courtney J. Mycroft-West; Mark A. Skidmore; Anja Winter (Pathogens, 2020)
Dengue fever is a rapidly emerging vector-borne viral disease with a growing global burden of approximately 390 million new infections per annum. The Dengue virus (DENV) is a flavivirus spread by female mosquitos of the aedes genus, but the mechanism of viral endocytosis is poorly understood at a molecular level, preventing the development of effective transmission blocking vaccines (TBVs). Recently, glycosaminoglycans (GAGs) have been identified as playing a role during initial viral attachment through interaction with the third domain of the viral envelope protein (EDIII). Here, we report a systematic study investigating the effect of a range of biologically relevant GAGs on the structure and oligomeric state of recombinantly generated EDIII. We provide novel in situ biophysical evidence that heparin and chondroitin sulphate C induce conformational changes in EDIII at the secondary structure level. Furthermore, we report the ability of chondroitin sulphate C to bind EDIII and induce higher-order dynamic molecular changes at the tertiary and quaternary structure levels which are dependent on pH, GAG species, and the GAG sulphation state. Lastly, we conducted ab initio modelling of Small Angle Neutron Scattering (SANS) data to visualise the induced oligomeric state of EDIII caused by interaction with chondroitin sulphate C, which may aid in TBV development.